Detection of Pyricularia oryzae Based on Indirect ELISA Using Germinating Conidia as the Antigen Preparation - Masdor, Noor Azlina; Rani, Rashid Mat; Yahya, Aseha; Awaluddin, Norhafniza; Salam, Faridah; Jack, Allicia (Journal of Environmental Microbiology and Toxicology, 2017)
One of the most destructive fungal diseases in rice crop in Malaysia is the Rice blast disease or Penyakit Karah, which is caused by Pyricularia oryzae Cav. (previously known as Magnoporthe grisea). The disease can cause a loss of yield of more than 50 percent. In this study a sensitive indirect ELISA method was developed for the detection of Pyricularia oryzae through an indirect ELISA method using rabbit polyclonal antibody against different concentrations of Pyricularia oryzae conidia to give seven calibration standard points ranging from 1Ã—101 to 1Ã—109 conidia/mL. The calibration curve shows a typical sigmoidal curve and the fitting of the curve was based on the four-parameter logistic equation. The calculated LOD value was 21.60 conidia/mL (95% confidence interval, 11.63 to 31.57 conidia/mL) with a good correlation coefficient value of 0.999 indicating the model fit the experimental data in an excellent manner. The sensitivity was comparable to another published work which claimed to be the most sensitive to date. This indicate that the current developed method can be utilized in the future as a sensitive method for the rapid and simple detection of this pathogen.